Disidentify. Postmodern critiques of identity (Cultura Económica, 2022)
The classical paradigm, according to which the key to life consists in the development of one's own identity, must be overcome. The proposal for a progressive “identification” is an imposture that must be “denatured” and, therefore, “deconstructed”, since it depends on a historical project of power. J. RanciÁ¨re and P. B. Preciado, among others, promote, in response, an ethical model of “disidentification”. Human existence should advance, leaving behind at every step what until then was considered one's own identity. In these lines, the philosophical foundations of this idea are analyzed, its presence in some contemporary interdisciplinary debates is evaluated, and it is concluded that, in its most radical versions, it constitutes an "ontology of the impossible" (Preciado, 2019: 285).
Keywords: DECONSTRUCTION; IDENTITY; DISIDENTIFICATION; POSTMETAPHYSICS; BIOPOLITICS